Images in Medical Practice: A Patient with Rare Cause of Restricted Mouth Opening - Sadat, SM Anwar; Rita, Sufia Nasrin; Khan, Mahfujul Haq (Journal of Bangladesh College of Physicians and Surgeons, 2011)
DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7958 (J Bangladesh Coll Phys Surg 2011; 29: 109-110)